Conservation practices reverse soil degradation in Mediterranean fig orchards - Dugan, Ivan; Pereira, Paulo; Barcelo, Damia; Bogunovic, Igor (Geoderma Regional, 2024)
Agriculture is an important driver of soil degradation, especially where intensive practices are applied. It is essential to reduce the impact of agriculture intensification and find different solutions to halt this. This work investigates the effect of different types of treatments: 1) tillage (Tilled), 2) Grass covered (Grass), 3) olive pomace (Pomace) and 4) Hay in different seasons (Spring, Summer, and Fall) using rainfall simulations (58 mm h−1 for 30 min). Tillage reduced bulk density (BD) compared to treatments with mulch cover. Grass-covered treatments increased soil organic matter (SOM) and water-stable aggregates (WSA). Additionally, they enhanced hydrological properties, thus mitigating sediment loss (SL) and element transport. The principal component analysis (PCA) showed strong relations between SL and element losses, as well as P soil and Cu soil with SOM. Thus, implementing soil conservation practices, such as hay used as a surface cover, is crucial for fig orchards and agricultural area management to reduce soil erosion, enhance soil quality, and mitigate element transport and SL. Further on, continuous monitoring of soil properties and hydrological responses throughout different seasons should be prioritized, along with exploring alternative methods to ensure sustainable soil management.